China as a Sea Power, 1127-1368 : A Preliminary Survey of the Maritime Expansion and Naval Exploits of the Chinese People During the Southern Song and Yuan Periods - Lo, Jung-pang (NUS Press, 2012)
Lo Jung-pang argues that during each of the three periods when imperial China embarked on maritime enterprises (the Qin and Han dynasties, the Sui and early Tang dynasties, and Song, Yuan, and early Ming dynasties), coastal states took the initiative at a time when China was divided, maritime trade and exploration subsequently peaked when China was strong and unified, and declined as Chinese power weakened. At such times, China's people became absorbed by internal affairs, and state policy focused on threats from the north and the west. These cycles of maritime activity, each lasting roughly five hundred years, corresponded with cycles of cohesion and division, strength and weakness, prosperity and impoverishment, expansion and contraction.